GREEN INTELLECTUAL CAPITAL, GREEN INNOVATION AND GREEN TRAINING FOR ENVIRONMENTAL SUSTAINABILITY– EVIDENCE FROM THE PALESTINIAN BANKING SECTOR - Barakat, Anwaar (An-Najah National University, 2024)
The notable incremental demand for environmental performance in the banking sector has created a massive need to examine how green practices influence ecological performance. This study aims to investigate the impact of Green Intellectual Capital (GIC), Green Innovation (GI), and Green Training (GT) on Environmental Performance (EP) in the Palestinian banking sector, providing insights to improve sustainability practices. The sampling plan for this research included selecting 97 managers from 12 different Palestinian banks as the target population, given their direct engagement in green initiatives implementation. A quantitative research approach was used, and data was collected through structured questionnaires. The sample size was determined to ensure a representative group of employees across multiple banks, capturing diverse GIC, GI, and GT perspectives. This sample allowed for using Structural Equation Modeling (SEM) techniques to analyze the relationships between the variables. The findings confirm a strong and positive correlation between Green Intellectual Capital and EP, meaning that the more a bank adheres to environmental principles, the more likely it is to record better ecological results. Moreover, the result proves a positive relationship between GI and EP. This result highlights the importance of innovation activities in maintaining a sustainable environment. The study also stresses the significance of GT in enhancing Green Intellectual Capital and GI and in promoting the culture for ecological development. This study is helpful to policymakers and bank management in Palestine as they can apply some recommendations on sustainable practices in the banking system. The results will help to expand the knowledge of the concept of sustainability in the context of the banking field and provide further groundwork for more investigations of the establishment of sustainable practices in the financial sector.
رأس المال الفكري الأخضر والابتكار الأخضر والتدريب الأخضر من اجل الاستدامة البيئية: أدلة من القطاع المصرفي الفلسطيني